2015
DOI: 10.3109/17435390.2015.1039092
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Au, ZnO and SiO2NPs usingin vitroassays with mussel hemocytes and gill cells: Relevance of size, shape and additives

Abstract: Metal-bearing nanoparticles (NPs) possess unique physico-chemical characteristics that make them useful for an increasing number of industrial products and applications, but could also confer them a higher toxicity due to their higher reactivity compared to bulk forms of the same materials. There is a considerable interest in the use of in vitro techniques in environmentally relevant species, such as marine mussels, to evaluate NPs toxicity. In the present work, mussel hemocytes and gill cells were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…50,51 For instance, the toxic threshold for soluble GO is lower than hydrophobic graphene in C. elegans …”
Section: Discussionmentioning
confidence: 99%
“…50,51 For instance, the toxic threshold for soluble GO is lower than hydrophobic graphene in C. elegans …”
Section: Discussionmentioning
confidence: 99%
“…For example, Canesi et al (2010) found that nanoscale titanium dioxide (nano-TiO 2 ) induced toxic effects on the mussel M. galloprovincialis at 1-10 mg L −1 concentration. Compared with other kinds of NPs, metal-bearing NPs, especially nano-TiO 2 , are produced at the highest amounts (Katsumiti et al, 2016). The extensive applications of nano-TiO 2 will lead to an increased environmental concentration of titanium (Hall et al, 2009) that poses a potential risk to aquatic organisms (Kaegi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…27,34,35 As with all NPs, AuNPs have varying degrees of cytotoxicity, which is dependent on their size, [36][37][38] surface chemistry, 35,[39][40][41] shape 34,42,43 and most importantly dosage. 18 Various trends in size-dependent cytotoxicity have been observed, most commonly showing an increased cytotoxicity for smaller sized NPs, particularly those ,5 nm.…”
Section: Introductionmentioning
confidence: 99%